Wavelength Optimisation in a Spectroscopy System for Wide-Range Uric Acid Detection - Yaacob, Afiqah; Ngajikin, Nor Hafizah; Che Abd Rashid, Nurfatihah; Ali, Siti Hajar Aminah; Yaacob, Maslina; Zainal, Nurfarina; Ian Yulianti,; Cholan, Noran Azizan (International Journal of Integrated Engineering, 2025)
This study demonstrates a wide linearity range for uric acid sensing in the visible and near-infrared spectrum using direct spectroscopy detection, eliminating the need for enzymes or reagents. The system was experimentally tested across a uric acid concentration range of 10 to 200 mg/dL, exhibiting excellent performance in linearity, sensitivity, and accuracy, with optimal results observed at a wavelength of 950 nm. At this wavelength, the sensor achieved a linearity of 0.9694, sensitivity of 0.0034 (mg/dL)⁻¹, and accuracy of 97.42%. Compared to the previous developments, this work validates the improved linearity range performance and offers rapid response times due to its reagent-free design. The proposed sensor shows strong potential for efficient real-time monitoring of uric acid over a wide concentration range.